(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2025)
This study investigated the development of a multi-tiered blended learning ecosystem in higher education that integrates adaptive technologies, family engagement, and psychological literacy development. By examining the interplay among these components, this study endeavors to enhance students’ digital innovation skills and improve their overall learning outcomes. The proposed model utilizes adaptive technologies to personalize learning pathways and foster individualized education. Simultaneously, family engagement is considered a crucial factor in reinforcing a supportive learning environment and bridging the gap between the domestic and academic settings. The incorporation of psychological literacy development aims to equip students with critical thinking, emotional regulation, and collaborative skills that are essential for navigating digital innovation. These findings contribute to the extant literature on blended learning frameworks, offering actionable insights into creating inclusive and adaptive education systems in the digital era.